2019
DOI: 10.1042/bst20190763
|View full text |Cite
|
Sign up to set email alerts
|

Understanding PDE4's function in Alzheimer's disease; a target for novel therapeutic approaches

Abstract: Phosphodiesterases (PDEs) have long been considered as targets for the treatment of Alzheimer's disease (AD) and a substantial body of evidence suggests that one sub-family from the super-family of PDEs, namely PDE4D, has particular significance in this context. This review discusses the role of PDE4 in the orchestration of cAMP response element binding signaling in AD and outlines the benefits of targeting PDE4D specifically. We examine the limited available literature that suggests PDE4 expression does not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 84 publications
2
31
0
Order By: Relevance
“…PDE4D transcript has also been shown to be decreased in AD in the hippocampus, which may be related to neuronal loss (McLachlan et al, 2007). However, mRNA is not always indicative of protein levels, and there is still debate over the changes in PDE4D activity with age (Tibbo et al, 2019). Nonetheless, the current results demonstrated that PDE4D protein levels are significantly decreased in the aged FC, supporting human transcriptome studies.…”
Section: Pde4d In Aging and Adsupporting
confidence: 75%
See 3 more Smart Citations
“…PDE4D transcript has also been shown to be decreased in AD in the hippocampus, which may be related to neuronal loss (McLachlan et al, 2007). However, mRNA is not always indicative of protein levels, and there is still debate over the changes in PDE4D activity with age (Tibbo et al, 2019). Nonetheless, the current results demonstrated that PDE4D protein levels are significantly decreased in the aged FC, supporting human transcriptome studies.…”
Section: Pde4d In Aging and Adsupporting
confidence: 75%
“…cAMP-PKA Signaling in the FC vs. Hippocampus cAMP-PKA signaling is traditionally associated with enhanced plasticity and learning, e.g., in primitive organisms (Dudai et al, 1976;Tibbo et al, 2019), and in classic brain circuits such as the hippocampus (Kandel, 2012). However, cAMP signaling can impair the working memory functions of the newly evolved PFC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PDE11A4 also plays a role in systems consolidation, which has relevance for cognitive de cits [33]. Phosphodiesterases (PDEs) have been linked to mental processes of emotions, learning and memory, with implications in mood and cognitive disorders, including Huntington disease, Parkinson's disease and AD [34][35][36][37]. This evidence suggests that PDE11A plays a role in brain function and may also be involved in AD.…”
Section: Discussionmentioning
confidence: 99%